Wacana Tubuh Di Media Sosial Instagram: Studi Pendekatan Sosiologi Pengetahuan Karl Mannheim - Anita, Ningsih; ., Fauzan; Lisari, Melva Veronika (Indonesian Journal of Islamic Theology and Philosophy, 2023)
Abstract;This research aims to examine body problems that are often displayed on social media. where the body should not be for public consumption or spectacle, should not be changed and modified properly so that it becomes a discourse on Instagram social media. This research wants to examine how people's discourse and knowledge about the body on Instagram social media. This research is a type of library research, with the nature of the research being a deductive qualitative method in the field of philosophy with Karl Mannheim's sociology of knowledge approach. In this research it was found that first; body discourse on Instagram social media is produced by the capitalist system. Second; Public knowledge based on objective meaning is always characterized by physical beauty, white skin, sexy body, long hair, and being able to attract attention. Expensive meaning, tattoos in modern culture or popular culture have become art which is actually presented as aesthetic beauty. Based on the meaning of the documentary, there are three forms of discourse that are discussed regarding the body, namely, the discourse on the commodification of women's bodies (capitalist system) which includes, the body being used as an advertising model and product icon, women's bodies being exploited as well as discourse on the objectification of women's sexuality, and the discourse on tattoos and body modification.Keywords:Body discourse; Instagram; Social Media. Abstrak;Penelitian ini bertujuan untuk mengkaji problematika tubuh yang sering dipertontonkan pada media social. dimana tubuh yang tidak seharusnya menjadi konsumsi atau tontonan publik, tidak seharusnya dirubah dan dimodifikasi sebagaimana mestinya sehingga menjadi wacana dalam media sosial instagram. Penelitian ini ingin mengkaji bagaimana wacana dan pengetahuan masyarakat tentang tubuh di media sosial Instagram. Penelitian ini merupakan jenis penelitian kepustakaan (Library Research), dengan sifat penelitian berupa metode kualitatif deduktif pada bidang filsafat dengan pendekatan sosiologi pengetahuan Karl Mannheim. Dalam penelitian ini ditemukan bahwa pertama; wacana tubuh di media sosial instagram di produksi oleh sistem kapitalisme Kedua; pengetahuan masyarakat berdasarkan makna objektif selalu ditandai dengan kecantikan fisik, berkulit putih, bertubuh seksi, rambut panjang, dan dapat menarik perhatian. makna ekspensive, tato dalam budaya modern atau budaya populer menjadi seni yang justru ditampilkan sebagai estetika keindahan. Berdasarkan makna dokumenter, terdapat tiga bentuk wacana yang diperbincangkan terkait tubuh yaitu, wacana komodifikasi tubuh perempuan (sistem kapitalis) yang meliputi, tubuh dijadikan sebagai model iklan dan icon produk, tubuh perempuan dieksploitasi serta wacana tubuh objektifikasi seksualitas perempuan, dan wacana tato dan modifikasi tubuh.Kata Kunci:   Instagram; Media Sosial; Wacana Tubuh.